Transformation of community education management in the digital era - Indri Ayu Widiyanti; Mohamad Fikri Fakhriyan (Priviet Social Sciences Journal, 2026)
Digital transformation has brought significant changes to all sectors of life, including community education management. Various efforts are made to continue to transform the management of community education to suit the needs and rapid changes of the times. This article aims to describe the dynamics of community education management transformation in the digital era with a focus on the opportunities and challenges faced. A qualitative descriptive approach and literature study were used to identify various studies that lead to the transformation of community education management. This study has shown that community digitalization offers great opportunities in terms of service efficiency and expansion and innovation of data-based programs and community participation. However, the main challenges faced by practitioners are the digital divide, limited human resource capacity, and institutions readiness are still obstacles in optimizing this transformation. The findings in this article are expected to help support policy formulation and the development of innovative and sustainable managerial practices to support community education in the digital community.